2022
DOI: 10.1071/an21395
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of reduced protein diets with

Abstract: Context. The impact of necrotic enteritis (NE) on acute-phase proteins, interleukins, blood mineral profiles, and gene expression have not been well documented. Aims. This study aimed to determine the effects of L-arginine (Arg) or L-citrulline (Cit) supplementation on serum immunological parameters, serum mineral composition and gene expression in broilers fed reduced-protein diets (RP) during subclinical NE challenge. Methods. Ross 308 cockerels (n = 720) were randomly assigned to six experimental treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Other studies have similarly shown variability in tight junction gene expression responses across different studies and NE-challenge models. For example, Dao et al (38) reported that an Eimeria challenge at 9 days of age followed by C. perfringens challenge at 14 days of age did not alter the expression of CLDN-1 in the jejunum of broilers at 16 days of age, but did reduce expression of CLDN-5 by 21% vs. unchallenged control birds, whereas Yuan et al (39) reported that occludin and CLDN1, but not CLDN2 or ZO-1, showed reduced expression (by 53% and 32%, respectively), in ileal samples taken at 28 days of age following a NE challenge (that comprised inoculation of 2.0 3 10 8 CFU of C. perfringens per day during 15–22 days of age). These changes were accompanied by a 12% reduction in average daily gain (ADG) and a 19-point increase in FCR during 22–28 days of age, confirming the link between effects on tight junction protein expression and impaired gross performance, as was also observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have similarly shown variability in tight junction gene expression responses across different studies and NE-challenge models. For example, Dao et al (38) reported that an Eimeria challenge at 9 days of age followed by C. perfringens challenge at 14 days of age did not alter the expression of CLDN-1 in the jejunum of broilers at 16 days of age, but did reduce expression of CLDN-5 by 21% vs. unchallenged control birds, whereas Yuan et al (39) reported that occludin and CLDN1, but not CLDN2 or ZO-1, showed reduced expression (by 53% and 32%, respectively), in ileal samples taken at 28 days of age following a NE challenge (that comprised inoculation of 2.0 3 10 8 CFU of C. perfringens per day during 15–22 days of age). These changes were accompanied by a 12% reduction in average daily gain (ADG) and a 19-point increase in FCR during 22–28 days of age, confirming the link between effects on tight junction protein expression and impaired gross performance, as was also observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the inhibition of mitochondrial respiration can decrease the transmembrane potential, leading to the release of cytochrome-c, which interacts with the cytoplasmic apoptosis activating factor-1 (Apaf-1) and procaspase-9 initiating the apoptotic cascade (Potoka et al, 2002). Previous research findings indicate an upregulation of NOS gene expression, increased gut permeability, and decreased expression of tight junction proteins and nutrient transporters during necrotic enteritis (Dao et al, 2022d). However, NO can play a significant role in the resolution of enteritis as well.…”
Section: Arginine and Necrotic Enteritismentioning
confidence: 99%
“…Hence, it is hypothesized that arginine supplementation will improve the immune response, gut barrier integrity, and growth performance of the birds during NE in broilers. Though there are previous studies on the effects of arginine supplementation in broilers during NE, these studies were conducted using reduced protein diets, which are not yet a standard practice in the commercial broiler industry ( Hilliar et al, 2020 ; Dao et al, 2022a ; Dao et al, 2022b ; Dao et al, 2022c ). The objective of this study was to assess the impact of arginine supplementation on the growth performance, intestinal pathology, and immune response of the birds during the NE challenge, using a diet prepared to meet or exceed the Cobb-500 nutrient requirements.…”
Section: Introductionmentioning
confidence: 99%